2016
DOI: 10.1017/thg.2016.56
|View full text |Cite
|
Sign up to set email alerts
|

Intrapair Comparison of Life-Course Appetite and Physical Activity in Elderly Danish Twins: Reliability and Association With Subsequent Survival

Abstract: Avoiding overeating and being physically active is associated with healthy aging, but methodological issues challenge the quantification of the association. Intrapair comparison of twins is a study design that attempts to minimize social norm-driven biased self-reporting of lifestyle factors. We aimed to investigate the association between self-reported lifestyle factors and subsequent survival in 347 Danish twin pairs aged 70 years and older and, additionally, to investigate the reliability of these self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In addition, the majority of studies have found positive correlations between physical activity and longevity in rodents (Bronikowski et al, ; Holloszy, ; Holloszy, Smith, Vining, & Adams, ; Lokkegaard, Larsen, & Christensen, ; Mlekusch et al, ; Vogel et al, ) as well as humans (Lokkegaard et al, ; Rizzuto & Fratiglioni, ; Vogel et al, ). In normal weight individuals, regular physical activity has been estimated to extend life by 7.2 years, and conversely, inactivity to decrease life by 3.1 years (Moore et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of studies have found positive correlations between physical activity and longevity in rodents (Bronikowski et al, ; Holloszy, ; Holloszy, Smith, Vining, & Adams, ; Lokkegaard, Larsen, & Christensen, ; Mlekusch et al, ; Vogel et al, ) as well as humans (Lokkegaard et al, ; Rizzuto & Fratiglioni, ; Vogel et al, ). In normal weight individuals, regular physical activity has been estimated to extend life by 7.2 years, and conversely, inactivity to decrease life by 3.1 years (Moore et al, ).…”
Section: Discussionmentioning
confidence: 99%